Joseph Dunne: Back to the Rough Ground: 'Phronesis' and 'Techne' in Modern Philosophy and in Aristotle. Notre Dame University Press. Notre Dame 1993. 492 pp. - Bay, Sergio Aguilar-Álvarez (Tópicos, Revista de Filosofía, 2013)
.